University of Antioquia Doctorate in Nursing opening. Trajectory, fundaments and hopes - Castrillón Agudelo, María Consuelo (Investigación y Educación en Enfermería, 2010)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Words pronounced by the Magíster María Consuelo Castrillón in August 17th of 2010. Historical date in which the Nursing Faculty of the University of Antioquia started the academic activities of its first doctorate program. From the perspective of this teacher who has been involved in the Nursing Doctorate project since the beginning, become a reality today, we remember the path and its basis, and she tells us the hopes for this doctoral training program.